PERANAN CAMAT DALAM MENJAMIN KESEHATAN DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2015 - Wiris Andespi Dier; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to examine the role of the handsome camat in ensuring environmental health in the district handsome Pekanbaru city in 2015, where the role of the handsome camat is to create a healthy environment sub-district, clean and indah.Dalam analyze and explain the results of this study, the authors use qualitative research and analysis in this study used qualitative data analysis.Results of research on the role camat handsome in ensuring the health of the environment in the district of handsome town pekanbaru 2015 shows that the role camat handsome city of Pekanbaru in ensuring the health of the environment in the district of handsome town pekanbaru 2015 is to mangadakan outreach to the community concerned, an approach to community leaders , held fostering of community institutions and control the field so that the inhibiting factors in the effort to realize the business can be suppressed and the purpose of the implementation of the program in ensuring the health of the environment in the district of handsome can be done well.Keywords: Role, District, Environmental Health